The Effect Of Local Government Commitment And Audit Opinion On Disclosure Of Local Government Financial Reports In Indonesia - Monica Puspita Sari; Binsar H Simanjuntak (Al-Makki Publisher, 2022)
In this study, the authors are interested in examining how the influence of heads of local government commitment and audit opinions on the disclosure of local government financial statements in Indonesia with the level of public education as a moderating variable. This study used a population of all provinces in Indonesia from 2019 to 2021, totaling 34 samples, according to the criteria needed in this study. This study uses logistic regression analysis with the results of the study that heads of local government commitment has a positive effect on local government financial statement disclosures, and audit opinions have a positive effect on local government financial statement disclosures. The level of education moderation variable can only strengthen the positive influence of heads of local government commitment on local government financial statement disclosures and weaken the positive effect of audit opinions on local government financial statement disclosures.